DISKRIMINASI RASIAL DAN ETNIS SEBAGAI PERSOALAN HUKUM DAN HAK ASASI MANUSIA - Hesti Armiwulan (Faculty of Law, Universitas Diponegoro, 2015)
The Republic of Indonesia already had commitment to respect and uphold human rights that stipulated in The Constitution of Republic of Indonesia 1945. One of the constitutional rights is everyone have the rights to free from discrimination. The issue of potential racial discriminationoccurred in Indonesia, considered the amount of population in Indonesia is too many, a lot of different ethnic, racial and ethnic groups (multi-ethnic) and educational level is still relatively low as well as a lot of them are poor persons . The effort to eliminate racial discrimination is law protection and law enforcement as well as increasing awareness to respect human dignity.